Epigallocatechin gallate improves insulin resistance in HepG2 cells through alleviating inflammation and lipotoxicity. (August 2018) - Zhang, Qiao; Yuan, Hang; Zhang, Cong; Guan, Yue; Wu, Yuqing; Ling, Fan; Niu, Yucun; Li, Ying
Abstract: Aims: High levels of circulating free fatty acids (FFAs), inflammation and oxidative stress are important causes for insulin resistance (IR) and type 2 diabetes mellitus. The aim of this study was to investigate the mechanisms of EGCG in alleviating IR in HepG2 cells. Methods: HepG2 cells were treated with 25 mM glucose, 0.25 mM palmitic acid (PA), or 50 μM EGCG for 24 h. Results: EGCG increased glucose uptake and decreased glucose content. EGCG markedly decreased the levels of inflammatory and oxidative stress factors including nuclear factor κB (NF-κB), tumor necrosis factor-α, interleukin-6, reactive oxygen species, malondialdehyde and p53 protein, and markedly increased superoxide dismutases (SOD), glutathione peroxidase and SOD2 protein. EGCG significantly downregulated the levels of FFAs, triacylglycerol and cholesterol in HepG2 cells. The glucose transporter 2 (GLUT2) protein and its downstream proteins peroxisome proliferator-activated receptor γ coactivator (PGC)-1β were significantly increased, and sterol regulatory element-binding-1c (SREBP-1c) protein, and fatty acid synthase (FAS) were significantly decreased by EGCG in HepG2. Moreover, the foregoing effects were reversed by siRNA-mediated knockdown of GLUT2. Conclusion: Our data demonstrated that EGCG improved IR, possibly through ameliorating glucose (25 mM) and PA (0.25 mM)-induced inflammation, oxidative stress, and FFAs via the GLUT2/PGC-1β/SREBP-1c/FAS pathway in HepG2 cells.